Meningkatkan Efektivitas Organisasi Melalui Manajemen Diklat - Nasution, Abdul Fattah; Siregar, Nur Khofifah; Lubis, Melati Br.; Ramadhani, Putri Suci (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Increasing organizational effectiveness through management education and training (diklat). Training is an important instrument in human resource development which aims to increase employee competence, skills and knowledge. Through effective training management, organizations can ensure that the training programs held are relevant to the needs of the organization and employees, thereby increasing overall productivity and performance. This research highlights the importance of careful planning, structured implementation, and continuous evaluation in education and training management. Apart from that, active participation from top management and the use of information technology are also key factors in the success of training programs. Thus, good training management not only contributes to the individual development of employees, but also supports the achievement of the organization's strategic goals.